THE SHIFTING ROLES OF EYL TEACHERS IN THE DIGITAL NATIVE ERA - Karina Sari (Universitas Muhammadiyah Gresik, 2015)
The advancement of technologies has caused two distinct generations called as DigitalNative and Digital Immigrant. This two generation has made a shifting role for teachers ineducation, not to mention children education. Children nowadays to belong digital nativegenerations, meanwhile not all teachers are. Consequently, as teacher need to realize theneed of having applicable strategy to keep up with the technology advancement and fulfillthe learners need and preference in learning. Therefore, this article would like to proposeideas on the applicable practices in regard with the technology advancement in DigitalNative era with Digital Native learners of children.